Profitability determining factors of banking sector: Panel data analysis of commercial banks in South Asian countries - Yuan, Deli; Gazi, Md. Abu Issa; Harymawan, Iman; Dhar, Bablu Kumar; Hossain, Abu Ishaque (Frontiers in Psychology, 2022)
Aim of the article: The main purpose of this research is to investigate the impact of determinants of profitability on commercial banks in Asian countries. As Asian country Bangladesh and India has been selected as research field. The study also pursues to examine the impact of specific factors and macroeconomic factors on profitability in the Bangladeshi and Indian private commercial banking sector. Methods applied and analysis tools: Data retrieved from annual report of India and Bangladesh’s private commercial banks covering the period of 2010-2021. As sample 40 private commercial banks have been considered randomly, of which 20 is from India and 20 are from Bangladesh. Panel data research methodology has been used as an estimation technique to analyze the data. Also, OLS regression model used to scrutinize data. To check that the models were appropriate, the Breusch-Pagan Lagrange Multiplier Test was employed. Banks’ specific factors and microeconomic factors showed almost same variations for Bangladesh and India’s private banks. All models and tests were evaluated using E-views econometric software. Major findings: The study finds that explaining ROA from the banks’ specific variables, strength of Bank size (BS) and Debt to Asset Ratio (DAR) is positive and significant. For bank’s DTAR-Deposit to Asset Ratio, LDR-Loan to Deposit Ratio is also found negative and significant. EAR-Equity to Asset Ratio and DER-Debt to Equity Ratio has no any positive/negative impact. Contribution, Originality and Implications: As a macroeconomic variable, the rate of inflation (IR) and the rate of GDP growth (GDPGR) are measured positive and significant for ROA. As macroeconomic variables Inflation Rate (IR) and GDP Growth Rate (GDPGR) is found to be positive and significant in case of ROA